2019
DOI: 10.1186/s41935-018-0108-0
|View full text |Cite
|
Sign up to set email alerts
|

Firearm injuries in rural Saudi Arabia: incidence, patterns, management, and cost

Abstract: Background: A retrospective study from 2013 to 2017 was conducted to evaluate the incidence of small firearms and air gun injuries, social demographics of victims, severity of injuries, patterns, length of stay, and cost of hospitalization in highly populated central rural Al Kharj region of Saudi Arabia. Results: In total, the study included 102 cases. The incidence of firearms and air gun injuries in Al Kharj region was 3.13/100,000. Most of the victims were young-aged males (98 cases; 96.1%). The males were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Although these have been found to have the potential to cause fatal and grievous injuries such as bone micro-fracture (Kieser et al 2013), and ocular injuries (Schein et al 1994) and even may cause death (Lal and Subrahmanyam 1972). It is evident from the literature that air guns (both rifle and pistol) are being used in illicit activities for a long period and in current time also (Burnt and Packey 1979;Harshey et al 2017;Morgan et al 2019). Various researchers studied the different aspects of glass and air gun that may be of forensic interest such as wounding potential and behavior of air gun pellet in ballistic gel (DiMaio et al 1982;Wightman et al 2010;Hallikeri et al 2012;Stankov et al 2013…”
Section: Introductionmentioning
confidence: 99%
“…Although these have been found to have the potential to cause fatal and grievous injuries such as bone micro-fracture (Kieser et al 2013), and ocular injuries (Schein et al 1994) and even may cause death (Lal and Subrahmanyam 1972). It is evident from the literature that air guns (both rifle and pistol) are being used in illicit activities for a long period and in current time also (Burnt and Packey 1979;Harshey et al 2017;Morgan et al 2019). Various researchers studied the different aspects of glass and air gun that may be of forensic interest such as wounding potential and behavior of air gun pellet in ballistic gel (DiMaio et al 1982;Wightman et al 2010;Hallikeri et al 2012;Stankov et al 2013…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the KSA's civilian doctors will hardly ever get the opportunity to treat gun-related injuries. These injuries are primarily treated by military surgical services, local hospitals, and trauma centers [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The rate of violent deaths and related to firearm injuries in the developing societies are the twice as compared to high income countries 4 . A study conducted in the Northern Italy showed the mortality rates approximately 0.84 per every 100000 residents in year 2006, however the average of 12.6 cases yearly 5,6 .…”
Section: Introductionmentioning
confidence: 99%